2010
DOI: 10.1007/s12192-010-0192-z
|View full text |Cite
|
Sign up to set email alerts
|

The response of interleukin-6 and soluble interleukin-6 receptor isoforms following intermittent high intensity and continuous moderate intensity cycling

Abstract: As interleukin-6 (IL-6), its soluble receptor (sIL-6R), and the IL-6/sIL-6R complex is transiently elevated in response to prolonged moderate-intensity exercise, this study investigated how these levels would be modulated by an acute bout of high-intensity intermittent (HIIT) exercise in comparison to continuous moderate-intensity exercise (MOD). This study also investigated the expression of the differentially spliced sIL-6R (DS-sIL-6R) in response to exercise. Eleven healthy males completed two exercise tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
74
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 32 publications
9
74
2
Order By: Relevance
“…The execution of high-intensity bursts, with the accompanying rise in BLa, does not seem to have additional effects on the response of the cytokines measured in this study. This corroborates with studies examining the acute inflammatory response to different forms of cycling (Cabral-Santos et al 2015), although larger increases in IL-6 after HIIT compared to work-matched moderate continuous exercise have been found as well (Leggate et al 2010). Of note, as in the study of Leggate et al (2010), the main trials of the current study were matched for external work rather than energy expenditure.…”
Section: Cytokine Response To Upper-body Exercisesupporting
confidence: 91%
See 1 more Smart Citation
“…The execution of high-intensity bursts, with the accompanying rise in BLa, does not seem to have additional effects on the response of the cytokines measured in this study. This corroborates with studies examining the acute inflammatory response to different forms of cycling (Cabral-Santos et al 2015), although larger increases in IL-6 after HIIT compared to work-matched moderate continuous exercise have been found as well (Leggate et al 2010). Of note, as in the study of Leggate et al (2010), the main trials of the current study were matched for external work rather than energy expenditure.…”
Section: Cytokine Response To Upper-body Exercisesupporting
confidence: 91%
“…Typically, HIIT sessions take not more than 20 min and have been shown to be equally or even more effective in inducing cardiovascular adaptations (Gibala et al 2012) and improving performance (Milanović et al 2015) compared to moderate-intensity continuous exercise. Investigating the acute inflammatory response, Leggate et al (2010) and Wadley et al (2015) showed that the increase in IL-6 after HIIT was greater compared to moderate-intensity continuous exercise, although this finding has not consistently been shown in the literature (Cabral-Santos et al 2015;Kaspar et al 2016).…”
Section: Introductionmentioning
confidence: 97%
“…Data from previous experiments suggested that the net energy expenditure of exercise should be comparable between the high intensity and steady state exercise sessions (Leggate et al 2010;Warren et al 2009). …”
Section: Net Energy Expenditure Of Exercisementioning
confidence: 95%
“…In the latter, IL-6 is responsible for the suppression of pro-inflammatory cytokines (i.e. TNF-α) and the increase in circulating levels of anti-inflammatory cytokines, such as IL-10 and IL-1ra [2,15,16]. Thus, when exercising chronically, individuals maintain a more pronounced anti-inflammatory milieu, which protects them against low grade inflammatory processes.…”
Section: Production and Release Of Anti-inflammatory Cytokinesmentioning
confidence: 99%
“…Several research and review papers have been published on the topic [1][2][3][4]. Even though this area still requires further research, one thing is clear: chronic exercise exerts a positive effect on our body's immune system by decreasing the prevalence of chronic diseases.…”
mentioning
confidence: 99%